COMPUTER TOOLS TO AID THE LEARNING AND DESIGN STEPS FOR PHOTOVOLTAIC SYSTEMS - Sampaio, Leonardo P. [UNESP]; Brito, Moacyr A. G. de [UNESP]; Melo, Guilherme A. E. [UNESP]; Canesin, Carlos A. [UNESP]; IEEE (Ieee, 2011)
This paper presents novel simulation tools to assist the lecturers about learning processes on renewable energy sources, considering photovoltaic (PV) systems. The PV behavior, functionality and its interaction with power electronic converters are investigated in the simulation tools. The main PV output characteristics, I (current) versus V (voltage) and P (power) versus V (voltage), were implemented in the tools, in order to aid the users for the design steps. In order to verify the effectiveness of the developed tools the simulation results were compared with Matlab (R). Finally, a prototype was implemented with the purpose to compare the experimental results with the results from the proposed tools, validating its operational feasibility.
Keywords: Renewable Energy Sources; Photovoltaic Systems; Photovoltaic Modeling; Java Simulation Tools; Power Electronics